2004
DOI: 10.1111/j.0272-4332.2004.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Dead Reckoning: Demographic Determinants of the Accuracy of Mortality Risk Perceptions

Abstract: General patterns of bias in risk beliefs are well established in the literature, but much less is known about how these biases vary across the population. Using a sample of almost 500 people, the regression analysis in this article yields results consistent with the well-established pattern that small risks are overassessed and large risks are underassessed. The accuracy of these risk beliefs varies across demographic factors, as does the switch point at which people go from underassessment to overassessment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 21 publications
6
56
0
Order By: Relevance
“…The evidence that individuals overassess small fatality risks and overweigh small probabilities is undisputed (Lichtenstein et al 1978;Kahneman et al 1982;Prelec 1998;Hakes and Viscusi 2004), and inaccurate risk perception may result in biased WTP estimates (Gayer et al 2000;Bleichrodt and Eeckhoudt 2006). Johansson-Stenman and Martinsson (2006) found that, when examining which car attributes that are important for car consumers, nearly all car consumers considered safety to be very (ca.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence that individuals overassess small fatality risks and overweigh small probabilities is undisputed (Lichtenstein et al 1978;Kahneman et al 1982;Prelec 1998;Hakes and Viscusi 2004), and inaccurate risk perception may result in biased WTP estimates (Gayer et al 2000;Bleichrodt and Eeckhoudt 2006). Johansson-Stenman and Martinsson (2006) found that, when examining which car attributes that are important for car consumers, nearly all car consumers considered safety to be very (ca.…”
Section: Discussionmentioning
confidence: 99%
“…It may manifest itself in assuming that the probabilities of such an event are higher than scientists say, that the catastrophe will be larger than they say, or both, or in a focus on the qualitative aspects of risks noted above. Evidence of such outcomes is discussed in Adler (2003) and evidence that individuals overstate low probability events can be found in Hakes and Viscusi (2004).…”
Section: Objectives and Methodsmentioning
confidence: 99%
“…Previous studies have indicated that patients overestimate rare mortality-related risks and underestimate common risk. 23 Hakes and Viscusi 23 administered a safety risk survey on hypothetical risk situations to assess perceptions of risk related to various causes of death and the influence of demographic factors. Results indicated an overestimation of death by more than 300%.…”
Section: Adverse Event/adverse Experiencementioning
confidence: 99%